Electrorefining of aluminum alloy in ionic liquids at low temperatures - Kamavaram V.; Mantha D.; Reddy R.G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electrorefining of aluminum alloy (A360) in ionic liquids at low temperatures has been investigated. The ionic liquid electrolyte was prepared by mixing anhydrous AlCl3 and 1-Butyl-3- methylimidazolium chloride (BMIC) in appropriate proportions. The effect of the cell voltage temperature, and the composition of the electrolyte on the electrorefining process has been studied. The characterization of the deposited aluminum was performed using scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques. The influence of experimental parameters such as cell voltage and concentration of AlCl3 in the electrolyte on the deposit morphology was discussed. The composition of the aluminum deposits was analyzed using X-ray fluorescence spectrometer (XRF). Aluminum deposits with purity higher than 99.89 % were obtained. At a cell voltage of 1.0 V vs. Al/Al(III), the energy consumption was about 3 kWh/kg-Al. The main advantage of the process is low energy consumption compared to the existing industrial aluminum refining process.